Effect of sterilization on cadmium immobilization and bacterial community in alkaline soil remediated by mercapto-palygorskite. (15th March 2021) - Wang, Yale; Xu, Yingming; Huang, Qingqing; Liang, Xuefeng; Sun, Yuebing; Qin, Xu; Zhao, Lijie
Abstract: Cadmium (Cd) pollution in alkaline soil in some areas of northern China has seriously threatened wheat production and human health. However, there are still few effective amendments for alkaline soil, and the mechanism of amendments with a good immobilization effect remains unclear. In this study, soil sterilization experiments were conducted to investigate the effects of soil microorganisms on the immobilization of a novel amendment—mercapto palygorskite (MPAL) in Cd-contaminated alkaline soils. The results showed that the mercapto on the MPAL surface was not affected by autoclaving. Compared with the control, the available Cd concentration in 0.025% MPAL treatments decreased by 18.80-29.23% after 1 d of aging and stabled after 10 d of aging. Importantly, the immobilization of MPAL on Cd in sterilized soil was significantly better than that in natural soil due to the changes in Cd fractions. Compared with MPAL-treated natural soil, exchangeable Cd fraction and carbonate-bound Cd fraction in MPAL-treated sterilized soil decreased by 20.79–27.09% and 20.05–26.45%, while Fe/Mn oxide-bound Cd fraction and organic matter-bound Cd fraction increased by 17.77–22.68% and 18.85–27.32%. Phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) analysis found that the potential functions of the microbial community in normal and sterilized soil were different significantly. Soil sterilization increased the soil pH and decreased the arylsulfatase activity, but did not change the soil zeta potential and available sulfur. The changes in Cd fractions in MPAL-treated sterilized soil may be related to the reduction in the bacterial community and the changes in function microbial, but not to the soil properties. In addition, MPAL application had little effects on the bacterial community, soil pH value, zeta potential, available sulfur, and arylsulfatase. These results showed that the immobilization of MPAL on Cd in alkaline soil was stable and effective, and was not affected by soil sterilization and soil microorganism reduction. Graphical abstract: Image 1 Highlights: Mercapto-palygorskite increased stable Cd fractions in sterilized alkaline soil. Soil sterilization changed bacterial community, soil pH and arylsulfatase activity. Potential functions of bacterial communities in natural and sterilized soils are different. Effect of mercapto-palygorskite on Cd in alkaline soil is fast, stable, and eco-friendly. Abstract : The immobilization of MPAL in sterilized soil was significantly better than that in natural soil due to the changes in the abundance and functions of bacterial community.